The price of WAR: AMR - Rojas, Laura J; Lemonovich, Tracy L; Marshall, Steven H; Hirschfeld, Adam; Perez, Federico; Bonomo, Robert A (JAC-antimicrobial resistance, 2025)
The ongoing conflict in Ukraine has exacerbated the risk of MDR bacterial infections in war-injured patients. We present the case of a Ukrainian soldier who sustained a traumatic explosive injury to the bilateral lower extremities, underwent surgery and subsequently experienced an infection with a carbapenem-resistant . The isolate was subject to genomic WGS. This case study describes the successful management of a traumatic injury in a Ukrainian soldier infected with a carbapenem-resistant isolated from surgical wounds. WGS revealed a hypervirulent ST147 strain carrying multiple resistance and virulence factors, including . Treatment with ceftazidime/avibactam and aztreonam was effective. Ceftazidime/avibactam and aztreonam is highlighted as a promising regimen for MDR infections in conflict zones.